Marriage after divorce: the challenge for the Church of England - Woods, Timothy (Islam and Christian-Muslim relations, 2006)
The decision of the Church of England to permit the further marriage in church of people who have been previously divorced was taken after much reflection and debate. This paper offers a brief outline of the key issues that had to be faced, addressing questions arising from New Testament material, the tradition and context of the Church of England itself, and ways that doctrine has been formulated and has then evolved. In particular the question of the sacramentality of marriage is considered, because it is those with a ‘high’ view of marriage as sacrament who adopt the view that marriages cannot be dissolved. Some discussion is included regarding Anglican theological method, whereby scripture, tradition, reason and experience are brought to bear on the discernment of God's will for the Church. I conclude that recent changes allowing further marriage do not equate to encouraging divorce.